Considerations for a New Collective Quantified Goal - UN Trade; Development (United Nations, 2024)
This report explores lessons from the ongoing challenges with climate finance and more specifically the 100 billion goal, proposing a set of considerations for the NCQG to ensure it is an improved target. The report attempts to clarify some of the key issues around a new needs-based target, supporting Parties to deliver an NCQG consistent with PA commitments, enabling more ambitious climate-resilient development pathways in developing countries, and rebuilding trust for all.